Clinical features and genotypes of six patients from four families with horizontal gaze palsy with progressive scoliosis - Huang, Lijuan; Guo, Jianlin; Xie, Yan; Zhou, Yunyu; Wu, Xiaofei; Li, Hui; Peng, Yun; Li, Ningdong (Frontiers in Pediatrics, 2022)
Background Horizontal gaze palsy with progressive scoliosis (HGPPS) is a rare disorder mainly involved in ocular movement and spinal development. It is caused by a roundabout guidance receptor 3 (ROBO3) gene mutation. This study aimed to describe the clinical features of six patients with HGPPS and investigate the corresponding ROBO3 gene mutations. Methods Patients underwent detailed clinical and imaging examinations. Whole-exome sequencing was performed to detect nucleotide variations in the disease-causing genes of HGPPS. Results Six pathogenic variants were detected in the ROBO3 gene from six patients with HGPPS, including two novel compound heterozygous mutations, c.1447C > T (p.R483X) and c.2462G > C (p.R821P); c.1033G > C (p.V345L) and c.3287G > T (p.C1096F); a novel homozygous indel mutation, c.565dupC (p.R191Pfs*61); and a known missense mutation, c.416G > T (p.G139V). Patients with HGPPS had horizontal conjugated eye movement defects and scoliosis with variable degrees, as well as flattened pontine tegmentum and uncrossed corticospinal tracts on magnetic resonance imaging. Conclusion Our genetic findings will expand the spectrum of ROBO3 mutations and help inform future research on the molecular mechanism of HGPPS.